Impact of COVID-19 and Government Imposed Lockdown Restrictions on South African Audit Engagements - Mugabe, Tadiwanashe; Ndlovu, Jane; Van Zijl, Wayne (The Journal of Accounting and Management, 2022)
Objectives This study analyses the impact of COVID-19 and government-imposed lockdown restrictions on the gathering of audit evidence and the auditors’ communication with the client and other team members. Approach A quantitative approach is used to analyze the results of an electronic questionnaire consisting of 5-point Likert scale questions. LinkedIn was used to distribute the questionnaire to auditors, and 61 responses were obtained for analysis. Despite the small sample size, the Kruskal-Wallis test showed that there was no statistically significant difference between the factor scores with regard to age and the type of audit firm. As a result, the survey's results are applicable to the whole audit profession in South Africa. Results It was found that the respondents highly valued the training provided by their respective audit firms as an effective tool for assisting them to adjust to remote working. Many auditors used Microsoft Teams and/or Zoom, both of which were considered highly effective communication tools. Despite the significant challenges that arose in the audit evidence gathering process, the auditors are confident they were able to overcome these challenges and still ensure that sufficient and appropriate audit evidence was collected.